Delivering the evidence – skill mix and education for elder care. (February 2014) - Wolff, Mark S.; Schenkel, Andrew B.; Allen, Kenneth L.
Abstract : Objectives: To review the current status of dental curricula on elder care, and the current curricula regarding elder care, and it's effect on altering practitioner behaviors while addressing the needs of a growing North American elder population. Background: An impending crisis is looming over the oral healthcare of our aging population. At the same moment that life expectancy is being extended through increasingly complex healthcare improvements, the numbers of trained dental providers capable and interested in delivering the needed care is failing to grow at an adequate rate. Discussion: The skills necessary to manage these increasingly complex patients require an interprofessional approach capable of delivering care to sicker patients, in a variety of living accommodations, while managing a variety of care givers. The dental skills necessary to treat these elderly are modifications of skills students routinely learn in dental school. As a matter of fact, the skills students acquire to treat an adult patient population may be contrary to the basic skills necessary to manage the elderly dependent adult patient. Teaching students the nuance differences needed to properly diagnose and care for this population is a difficult task that must be taught in a contextual environment. Conclusion: Significant changes in the teaching of dental management of the elderly are critical within much of the education community. Just as teaching students to care for the pediatric population as general dentists, the clinical education must involve a sufficient number of quality experiences to address issues of both competency, that of the graduate to perform care independently, and attitudes, the actually willingness to treat the elderly.